Metal sulfide (Cu-Mn-S) loaded-gel like carbon matrix as the electrode material for coin cell supercapacitors - Noymak S. (2023)
Transition metal sulfide (TMSs) combined with conductive carbon matrixes have been developed and show potential for use as energy storage devices. In this report, gel like active material of cupper-manganese-sulfide (CMS) loaded on reduced graphene oxide (rGO)/carbon nanotube (CNTs) (CMS@GCs) composites were synthesized using a one-step hydrothermal method which produced a porous structure after freeze-drying. The CMS@GCs have globular morphology assembled from Nano sheets/tube with porous structure. The as-prepared CMS@GCs composites showed a surface area of 29.96 m2/g which possessed excellent electrochemical properties. The CMS@GCs’ were investigated as super capacitor electrodes having symmetrical coin cell structure. The electrochemical results revealed that the CMS@GCs active materials exhibited the specific capacitance of 174 Fg−1 at 0.1 Ag−1 (maintains 68 Fg−1 at 1 Ag−1) and they delivered the energy density of 5.5 Whkg−1 with power density of 48 Wkg−1. Additional stability testing showed that the cell displays lifetime with 78.94% retention after 2,500 charge/discharge cycles in coin cell. These results demonstrated that the synthesized material fabricated in present study can be expected to be a promising as an electrode material for potential application in energy storage devices.